Infrared Spectra Interpretations of Clay-Adsorbed Water in Relation to the "Anomalous" Water Controversy - Leonard, R. A. (Spectroscopy letters, 1971)
The nature of surface adsorbed water has been the subject of countless investigations. Much of the discussion has centered around the degree and strength of H-bonding to surface groups and between adjacent water molecules. 1,2 Water condensed into glass or quartz capillaries sometimes has unusual properties. This unusual water has been referred to as "orthowater," 3 "anomalous water," 4,5,6 and "polywater" 7,8 and was thought by some to be polymers of water formed by specific surface catalysis. 1-3 Several possible structures of "polywater" have been suggested which require formation of symmetrical or very strong H-bonds between water molecules. 4,6,7 Infrared spectra of polywater have been presented 7,8 and the strongest absorption band which appeared at 1595 cm −1 was assigned to the symmetric O-H-O bond. However, more recent investigations suggest that the observed polywater bands may actually be SO 4 2- , -COOH − , or HCO 3 − bands, impurities collected by surface diffusion, 9 or bands of a HNO 3 solution formed by corona discharge. 10 Other observers 11,12 suggest that polywater may be a hydrosol formed by surface contaminates.